人類命運共同體——對薩斯教授一文的回應: A Human Community of Shared Future: A Response to Professor Sass - WANG, Yu; YIN, Mei (International Journal of Chinese & Comparative Philosophy of Medicine, 2020)
LANGUAGE NOTE | Document text in Chinese; abstract in English only. The COVID-19 pandemic has changed every single person and every political and corporate body. Even now, the pandemic remains severe in many countries. Every day, more lives are lost to the disease, which has destroyed countless families. Every member of the human family, every being in this world, is a tree on the same mountain and a wave on the same sea. Any political body, regardless of its form and size, has the same individual biological attributes as the people it comprises. It seeks to preserve its life, further its interests, and avoid harm, fighting, and even war. The activities of a state or social group, like those of an individual, are ultimately directed toward survival. However, achieving this purpose requires greater cooperation for a group and state than for an individual. Thus, various crises may be resolved by breaking down the barriers of “meritocracy”; rejecting any form of narrow localism, even a kind of dogmatic geographic patriotism; discarding groundless accusations and suspicion; and allowing all of mankind to breathe the same air and share the same fate. DOWNLOAD HISTORY | This article has been downloaded 5 times in Digital Commons before migrating into this platform.